The Application of Coaching Techniques to Financial Issues - J Michael Collins; Collin M O'Rourke (Journal of Financial Therapy, 2012)
Financial coaching is emerging as a distinct approach to building personal financial capability. However, the term financial coaching refers to a wide array of interventions. This article reviews the literature in order to define financial coaching. Financial coaching includes helping individuals define financial goals, develop plans of action, and implement steps toward their goals. The coaching approach is designed to help people develop and sustain positive financial behaviors. This article also presents findings from three financial coaching field studies; the results suggest that working with a financial coach increases clients’ ability to focus on their financial goals and engage in positive financial behaviors. Despite these beneficial outcomes, the coaching field faces several challenges including a lack of practice standards and consistent outcomes measures.
Keywords: household finance; financial planning; financial counseling